Kreativitas Sebagai Jembatan Menuju Bisnis Internasional - Nasyuwah S Hasibuan; Hendra Ibrahim (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This scientific work aims to provide understanding and knowledge to readers and researchers about how important and big the influence of the element of creativity is to support MSMEs in Indonesia to be more successful not only in their own country but also abroad (internationally). International business is now not only engaged in trade and manufacturing but also transportation, tourism, advertising, etc. To adapt yourself as a business actor in this advanced era, creativity is the bridge. This research uses a qualitative approach with descriptive analysis method. The results of the research are that in the creative economy there are many visions that build Indonesia to become one of the world's economic powers in the creative economy by 2030. The six visions are, namely; (1) Bringing together all assets and potential to create an independent creative economy. (2) Create an orderly climate for developing creative industries. (3) Supporting creative innovation that has added value and competitiveness in international business. (4) Expanding the public's insight and appreciation for all things about the creative economy, and providing a good image of the creative economy to the public. (5) Building awareness and respect for IPR, one of which is intellectual property protection in copyright.